Opportunistic screening for alcohol use problems in adolescents attending emergency departments: an evaluation of screening tools. (26th March 2018) - Coulton, Simon; Alam, M Fasihul; Boniface, Sadie; Deluca, Paolo; Donoghue, Kim; Gilvarry, Eilish; Kaner, Eileen; Lynch, Ellen; Maconochie, Ian; McArdle, Paul; McGovern, Ruth; Newbury-Birch, Dorothy; et al.
Abstract: Objective: To estimate and compare the optimal cut-off score of Alcohol Use Disorders Identification Test (AUDIT) and AUDIT-C in identifying at-risk alcohol consumption, heavy episodic alcohol use, ICD-10 alcohol abuse and alcohol dependence in adolescents attending ED in England. Design: Opportunistic cross-sectional survey. Setting: 10 emergency departments across England. Participants: Adolescents ( n = 5377) aged between their 10th and 18th birthday who attended emergency departments between December 2012 and May 2013. Measures: Scores on the AUDIT and AUDIT-C. At-risk alcohol consumption and monthly episodic alcohol consumption in the past 3 months were derived using the time-line follow back method. Alcohol abuse and alcohol dependence was assessed in accordance with ICD-10 criteria using the MINI-KID. Findings: AUDIT-C with a score of 3 was more effective for at-risk alcohol use (AUC 0.81; sensitivity 87%, specificity 97%), heavy episodic use (0.84; 76%, 98%) and alcohol abuse (0.98; 91%, 90%). AUDIT with a score of 7 was more effective in identifying alcohol dependence (0.92; 96%, 94%). Conclusions: The 3-item AUDIT-C is more effective than AUDIT in screening adolescents for at-risk alcohol use, heavy episodic alcohol use and alcohol abuse. AUDIT is more effective than AUDIT-C for the identification of alcohol dependence.